Executive Functioning Moderates Responses to Appetitive Cues: A Study in Severe Alcohol Use Disorder and Alcoholic Liver Disease. - Logge, Warren B; Morley, Kirsten C; Haber, Paul S; Baillie, Andrew J (Alcohol & Alcoholism, 2019)
Aim To examine subjective and psychophysiological responses to appetitive cues during an alcohol cue reactivity task, and its relation to alcoholic liver disease and assess whether executive functioning is associated with appropriate regulation of cue-elicited responses in individuals with severe alcohol use disorder (AUD). Methods Seventeen treatment-seeking alcoholic liver disease patients and a control group of treatment-seeking severe AUD participants completed neuropsychological executive functioning measures (Stroop task; Trail-making test) and the cue reactivity task, whereby control (water) and alcohol beverage cues were presented, followed by respective recovery periods. Subjective alcohol craving and heart rate variability were recorded across the task. Results Overall cue reactivity and consequent recovery after cue offset during the cue reactivity task was observed, and alcoholic liver disease participants demonstrated a reduced overall recovery effect. Better Stroop performance related to greater overall and alcohol-specific cue reactivity within the control AUD group, and alcoholic liver disease participants showed dysfunctional activity regardless of executive functioning performance. No group differences in recovery effects according to executive functioning performance were seen. Conclusion Among patients with AUD, having alcoholic liver disease seems to reduce overall regulation of responses to eliciting cues. Executive functioning moderated the magnitude of responses during cue exposures in our AUD sample overall; having alcoholic liver disease did not appear to affect regulation related to executive functioning during recovery.